Pemanfaatan Media Sosial Humas Polda Riau Dalam Memberikan Informasi Kepada Publik - Afifah Ramlah; Welly Wirman (Lembaga Pengembangan Kinerja Dosen, 2023)
Social Media has enabled the birth of new forms of social and social organizations and then transformed into a